An Analysis of the Second Year Students’ Ability in Writing Discussion Text at English Education Study Program in Universitas Negeri Padang - Silva Husna; Fitrawati Fitrawati (Universitas Negeri Padang, 2020)
This research was about the students' ability in writing a discussion text seen from the rhetorical structure and lexico-grammatical feature of the text., with the topic of Cyber-Bullying. The research design was the descriptive research. The population of this study was second year students of English Education Study Program Academic Year 2018. The population was 151 students from 5 classes. The sample was taken by random sampling technique so that the number of samples obtained was 22 samples. The instrument used was a test of discussion text writing for 90 minutes. The students’ writings were analyzed using discussion text writing rubric related to the rhetorical structure and lexico-grammatical feature of the text. Based on this research, students' ability in writing discussion texts was in fair (2) condition. Although the ability of students to write discussion texts was in fair (2) condition by looking to the rhetorical structure and lexico-grammatical feature of the text, there are several parts of the text that students have not understood how to write them. Students were expected to understand how to write a good discussion text by paying attention to the rhetorical structure and lexico-grammatical feature of the text.Key words: Writing Ability, Discussion text